Axial compressive performance of steel reinforced fibrous concrete composite stub columns: Experimental and theoretical study. (December 2021) - Memarzadeh, Armin; Nematzadeh, Mahdi
Abstract: This study is aimed at addressing the experimental and theoretical investigation of the compressive behavior of steel reinforced concrete (SRC) composite columns containing steel fibers considering the stirrups' confinement effects. Variables used to fabricate and evaluate the performance of the steel reinforced fibrous concrete (SRFC) columns include the steel profile shape (both H -shaped and C -shaped), volume fraction of steel fibers ( 0, 0.75, and 1.25 % ), and spacing of stirrups ( 40, 65, and 130 m m ). In total, 36 short column specimens were fabricated and such parameters as the axial bearing capacity, compressive stress–strain curves, ductility, peak strain and toughness were investigated through the axial compression test. According to the results, the axial bearing capacity of concrete-confined steel columns was affected by the steel shape inside; the axial bearing capacity of H -shaped cross-section columns was more - due to their more confinement - than that of C -shaped ones. Although adding, and increasing the percentage of, steel fibers increased the columns' axial bearing capacity slightly (up to 6 % ), their ductility and energy absorption improved significantly. Increasing the spacing of stirrups from 40 to 130 m m not only resulted in a 12 % reduction in the axial bearing capacity, but also reduced the contribution of the composite action of both H - and C -shaped profiles by more than 70 % . Finally, as predicting the SRC column strength is important, relationships presented by ACIITG, A S 3600, C S A - A 23, E N 1994, J G J 138, and N Z S 3101 for the prediction of the axial bearing capacity were thoroughly studied and showed that all had ignored the confinement effects. Considering the latter, this study modified the relationships, corrected the predicted results and compared them with both the experimental results of this study as well as those of other researchers' which showed a good correlation between the results.